2021
DOI: 10.3389/fpsyg.2021.638398
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Intensity of Happy Expression on Social Perception of Chinese Faces

Abstract: Numerous studies have shown that facial expressions influence trait impressions in the Western context. There are cultural differences in the perception and recognition rules of different intensities of happy expressions, and researchers have only explored the influence of the intensity of happy expressions on a few facial traits (warmth, trustworthiness, and competence). Therefore, we examined the effect of different intensities of Chinese happy expressions on the social perception of faces from 11 traits, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Specifically, participants preferred being treated by a happy rather than an angry physician and evaluated a happy physician more positively. These findings are in line with research showing that happy people are often evaluated more positively on a wide variety of traits ( Li et al, 2021 ). Yet, for these ratings, there is no evidence that participants related the expressions to the situation.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, participants preferred being treated by a happy rather than an angry physician and evaluated a happy physician more positively. These findings are in line with research showing that happy people are often evaluated more positively on a wide variety of traits ( Li et al, 2021 ). Yet, for these ratings, there is no evidence that participants related the expressions to the situation.…”
Section: Discussionsupporting
confidence: 91%
“…More interestingly, for male faces, female participants recognised masked and unmasked equally well; for female faces, regardless of participant gender, were evaluated more poorly when they were masked than unmasked, suggesting that the bottom face halves could be more informative for estimating age of a female than a male. We did not expect these findings, but when considering evidence that the jaw, chin, and zygoma (cheekbone) are collectively crucial for the perception of facial femininity (Li et al, 2021 ; Mogilski & Welling, 2018 ), it is plausible the presence of face mask restricts the use of these perceptual cues for age estimation. This raises the question of the relative quality of age information used by eyewitnesses in their descriptions when a face was partially covered by a mask.…”
Section: Discussionmentioning
confidence: 86%
“…Complementary to Marini et al's study, we demonstrated that the reduction in perceived intensity of emotions was also moderated by wearing a transparent mask. The perceived intensity of facial emotions, particularly for happy faces, is critical in judging a person's social aspects (e.g., the person's warmth) in interpersonal situations ( Li et al, 2021 ). Because wearing a surgical mask reduces perceived intensity in both genuine (Duchenne) and social (non-Duchenne) smiles ( Sheldon et al, 2021 ), genuine smiles could be misclassified as social smiles, and social smiles could be viewed as neutral expressions when wearing a surgical mask.…”
Section: Discussionmentioning
confidence: 99%